Prototype Scale Model and Design of Temperature Control in Simulation and Microcontroller dspic Using State Space Representation - Berrio, Luis Humberto; Gómez, Esteban (Ingeniería Solidaria, 2016)
Introduction: this article is the result of the research “Controllers in simulation of investigation not associated to an institutional project” developed in 2012 by the Pontifical Bolivarian University in Medellin, Colombia. It describes the development of a temperature control system in a scaled prototype of a small cavity; analyzes the control method in simulation and demonstrates how to implement the algorithm in a microcontroller DSPIC using state space representation and power control per stage.Methodology: a static and dynamic analysis of the system is performed and the procedure is described to locate the parameters of the model.Results: they are presented graphically, using data obtained both in the simulation as in the physical implementation of the prototype. In the data is observed the behavior of the control system when confronted with changing temperature references and disturbances. Each of the improvements made to the control system enhances the expected answer, so that it reaches a stable state in approximately 4 minutes, when using the controller PID and the open control loop.Conclusions: the second order model selected for the system’s dynamic model has good precision and follows approximately the same form as the experimental dynamic curve. The controlled system takes about 4 minutes to reach a stable state when using the PID and the open control loop.
Keywords: PID controller; block diagram; state space representation; frontloading; temperature